Application of Polyacrylamide Gel Electrophoresis in Determining Y-Chromosomal Variations in the Malay Ethnic Group from Kelantan - Shazlin, Shaharudin (Universiti Sains Malaysia, 2006)
The application of polyacrylamide gel electrophoresis technique and microsatellite (or V-chromosome Short Tandem Repeat, Y-STR) loci in population genetic study is reviewed. Malay population in Kelantan was surveyed in order to address hypotheses of their origin. We employed a set of three Y-STR markers to the nonrecombining portion of the V-chromosome to estimate the allele frequencies among Malay ethnic group from Kelantan population. Five cc of blood samples were collected with informed consent of volunteers from the selected districts in Kelantan. We were able to identify nine paternally-unrelated males (for at least three to six generation) as our subjects. The DNA was extracted using Qiagen extraction kit, and three Y-STR markers that is DYS391, DYS392, and DYS393 were genotyped. The primers were sequenced and amplified. The amplified products were separated on 20/0 agarose gel and later with 8% non-denature polyacrylamide gel. The fragments were then visualized by UV light. Identification of alleles were verified by comparing peR product sizes with allelic ladders. Alleles frequencies were calculated. The Malay Kelantan have diversity both in terms of number of alleles and the evenness of their allele frequencies distribution. The observed distribution is clearly consistent with low levels of male gene flow between these patrilocal, Malay Kelantanese ethnic group. Bigger sample size and more Y-STR loci examined could give complete analysis of Y -Chromosome substructure in this population.